IRX3 and IRX5 collaborate during ovary development and follicle formation to establish responsive granulosa cells in the adult mouse. Issue 3 (8th June 2020) - Fu, Anqi; Koth, Megan L; Brown, Ryan M; Shaw, Sarah A; Wang, Linda; Krentz, Kathleen J; Zhang, Xiaoyun; Hui, Chi-chung; Jorgensen, Joan S
Abstract: Healthy development of ovarian follicles depends on appropriate interactions and function between oocytes and their surrounding granulosa cells. Previously, we showed that double knockout of Irx3 and Irx5 ( Irx3/5 DKO) in mice resulted in abnormal follicle morphology and follicle death. Further, female mouse models of individual Irx3 or Irx5 knockouts were both subfertile but with distinct defects. Notably, the expression profile of each gene suggests independent roles for each; first, they are colocalized in pre-granulosa cells during development that then progresses to include oocyte expression during germline nest breakdown and primordial follicle formation. Thereafter, their expression patterns diverge between oocytes and granulosa cells coinciding with the formulation and maturation of intimate oocyte–granulosa cell interactions. The objective of this study was to investigate the contributions of Irx5 and somatic cell-specific expression of Irx3 during ovarian development. Our results show that Irx3 and Irx5 contribute to female fertility through different mechanisms and that Irx3 expression in somatic cells is important for oocyte quality and survival. Based on evaluation of a series of genetically modified mouse models, we conclude that IRX3 and IRX5 collaborate in the same cells and then in neighboring cells to foster a healthy and responsive follicle. Long after these two factors have extinguished, their legacy enables these intercellular connections to mature and respond to extracellular signals to promote follicle maturation and ovulation. Abstract : IRX3 and IRX5 collaborate in the same and then in neighboring cells to foster the extension of cellular processes that connect the oocyte and neighboring granulosa cells within the primordial follicle to promote follicle integrity.